2009 International Conference on Parallel and Distributed Computing, Applications and Technologies 2009
DOI: 10.1109/pdcat.2009.78
|View full text |Cite
|
Sign up to set email alerts
|

CheCUDA: A Checkpoint/Restart Tool for CUDA Applications

Abstract: In this paper, a tool named CheCUDA is designed to checkpoint CUDA applications that use GPUs as accelerators. As existing checkpoint/restart implementations do not support checkpointing the GPU status, CheCUDA hooks a part of basic CUDA driver API calls in order to record the status changes on the main memory. At checkpointing, CheCUDA stores the status changes in a file after copying all necessary data in the video memory to the main memory and then disabling the CUDA runtime. At restarting, CheCUDA reads th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…CheCUDA [12] and CheCL [13] are C/R solutions for CUDA and OpenCL applications, respectively. Snapify provides C/R, migration, and swapping services for Intel ® Xeon…”
Section: Resilience For Offload-based Pmsmentioning
confidence: 99%
“…CheCUDA [12] and CheCL [13] are C/R solutions for CUDA and OpenCL applications, respectively. Snapify provides C/R, migration, and swapping services for Intel ® Xeon…”
Section: Resilience For Offload-based Pmsmentioning
confidence: 99%
“…The work is done by adding memory copying after the syncthreads() function. CheCUDA [5] hooks a part of CUDA driver API calls to record the modifications in main memory. VCCP and CheCUDA are not designed for general GPU applications.…”
Section: Related Workmentioning
confidence: 99%
“…Takizawa et al [13], [14] demonstrated the feasibility of migrating a GPU program from one node to another. This work is similar to ours.…”
Section: Related Workmentioning
confidence: 99%